Characterization of Corynebacterium pseudotuberculosis biofilm / Mohamad Fakhri Yaacob - Yaacob, Mohamad Fakhri (2021)
Caseous lymphadenitis (CLA) is a ruminant disease caused by Corynebacterium pseudotuberculosis, a Gram-positive facultative intracellular pathogen. To date, the biofilm formation by C. pseudotuberculosis is not well understood. The present work was performed to characterize C. pseudotuberculosis biofilm. Determination of biochemical composition, morphology, antimicrobial susceptibility pattern and whole-cell protein expression of C. pseudotuberculosis biofilm was carried out using Raman spectroscopy, field emission scanning electron microscopy (FESEM), microplate biofilm assay and sodium dodecyl polyacrylamide gel electrophoresis (SDS-PAGE) respectively. Results showed that the 24-h-old biofilm was characterized by Raman spectral peaks at 615 cm-1 (CCC symmetric bend phenyl ring), 668 cm-1 (Valine) and 825 cm-1 (Ring breath Tyr.) whilst the 48-h-old and 72-h-old biofilms were characterized by Raman spectral peaks at 1400 cm-1 (COOsym.), 1450 cm-1 (COO- sym.), 1581 cm-1 (Ring breath Trp.), 1650 cm-1 (COOasym.) and 1725 cm-1 (C-O str.). Raman spectra also revealed the biochemical heterogeneity in C. pseudotuberculosis biofilm. FESEM images clearly showed the biofilm cells which were surrounded by the extracellular matrix. Treatment with nalidixic acid, streptomycin, tetracyclin, ethylenediaminetetraacetic acid (EDTA) and dimethyl sulfoxide (DMSO) significantly (p < 0.05) inhibited the viability of C. pseudotuberculosis biofilm. The major protein bands of C. pseudotuberculosis biofilm were found to be in the range between 33.7 kDa and 150 kDa. Differential protein expression in C. pseudotuberculosis biofilm was observed following the treatment with antimicrobial agents. The present study suggests that the biochemical composition of C. pseudotuberculosis biofilm may vary across different developmental stages. Meanwhile, nalidixic acid, streptomycin, tetracyclin, EDTA and DMSO may be useful in the treatment of CLA.